Tumour necrosis factor-α induces macromolecule translocation in HIV-derived duodenal organoids - Masete, Kopano Valerie; Massarani, Alain S.; Schulzke, Jörg-Dieter; Epple, Hans-Jörg; Hering, Nina A. (Frontiers in Immunology, 2025)
BackgroundDisease progression from human immunodeficiency virus (HIV) infection to acquired immunodeficiency syndrome (AIDS) is marked by chronic immune activation, partly due to increased translocation of gut-derived microbial antigens. Elevated mucosal tumour necrosis factor-α (TNF-α) and resulting epithelial cell apoptosis may be the etiology. However, studies using carcinoma cell lines have failed to find a causal link, possibly due to cellular abnormalities related to the malignant transformation of these immortal cell lines.MethodsWe established intestinal organoid monolayers from healthy controls and HIV-infected adults and characterized their growth dynamics and cellular composition. We then examined the effects of HIV-associated cytokines on transepithelial resistance (TER), apoptosis and macromolecule translocation.ResultsOrganoid monolayers from HIV-infected patients grew similarly to healthy controls, forming confluent monolayers within one to two weeks containing enterocytes, Paneth, goblet and stem cells. IFN-γ synergized with TNF-α, allowing TNF-α to cause caspase-mediated apoptosis and TER reduction within 5 ± 3 hours, reflecting patient sample heterogeneity. This led to paracellular passage of 4 kDa Dextran and transcytosis of 44 kDa horse radish peroxidase, both of which could be blocked by pan-caspase inhibitor, Q-VD-Oph.ConclusionOur study confirms that intestinal organoid monolayers from biopsies of HIV-infected individuals can be used to study apoptosis-related epithelial barrier dysfunction and macromolecular translocation. We provide direct evidence that TNF-α-induced apoptosis triggered two pathways of macromolecular translocation: paracellular passage via apoptotic leaks and transcytosis. Therapies targeting apoptosis may be useful in preventing disease progression from HIV to AIDS.